Phase-Feeding the Beef Herd for Improved Feed Utilization - Matt Hersom (EDIS)
The dairy industry utilizes the concept of differences in nutrient requirements of different cows within the herd and manages nutrient supply accordingly. In that regard, the dairy industry approaches different cow nutrient requirements by implementing phase feeding in the cow herd. Phase feeding is defined as: changing the nutrient concentrations in a series of diets formulated to meet an animal's nutrient requirements more precisely at a particular stage of growth or production. Phase feeding in the dairy industry is implemented based on placing cows into multiple feeding groups based on their lactation status. The phase feeding strategy is utilized to address the different nutrient requirements associated with milk production intensity. The dairy industry addresses the nutrient requirements of cows not on a singular basis but on a multiple nutrient basis.  This document is AN157, one of a series of the Animal Sciences Department, UF/IFAS Extension. Original publication date October 2005.